Activation of NF-kB pathway by virus infection requires Rb expression. - Maria A Garcia; Pedro Gallego; Michela Campagna; José González-Santamaría; Gloria Martínez; Laura Marcos-Villar; Anxo Vidal; Mariano Esteban; Carmen Rivas (PLoS ONE, 2009)
The retinoblastoma protein Rb is a tumor suppressor involved in cell cycle control, differentiation, and inhibition of oncogenic transformation. Besides these roles, additional functions in the control of immune response have been suggested. In the present study we investigated the consequences of loss of Rb in viral infection. Here we show that virus replication is increased by the absence of Rb, and that Rb is required for the activation of the NF-kB pathway in response to virus infection. These results reveal a novel role for tumor suppressor Rb in viral infection surveillance and further extend the concept of a link between tumor suppressors and antiviral activity.